Investigation of Workers' Food and Suggestions as to Dietary - Hill, Leonard, Sir, 1866- (London : His Majesty's Stationery Office)
1917-10 1917 1910s 12 pages 12 need 2½ times, men and very active boys three times the energy value of the ration. Workers doing heavy labour require 3½ times. Some doing very heavy work even four times the energy value of the ration. It is clear then that if the sedentary workers are to carry out the Food Controller's instructions and eat less than the ration of bread, and manual workers are to keep as close to the ration as possible, large amounts of other foods must be eaten. Therefore, since before the war, bread, meat, and sugar made up two-thirds of the food, and the other food only one-third, it is clear that to carry out the ration other and new sources of food supply must be forthcoming. These may either be used to substitute bread, or to increase the supply of breadstuffs. The latter is most economic for it saves time and fuel in cooking. It also least disturbs the national habit. Fortunately there is a supply in the oats and maize, peas, beans, and potatoes on which domestic animals are fed, also the barley which has partly gone to make beer, and partly to feed domestic animals. The country produces abundant stocks of grass, hay, straw, and roots for feeding the animals. Horses used for pleasure can be put out to grass, and their oats saved for man. Cattle can be killed as young beef, and the maize and other concentrated foods hitherto used for over-fattening reserved for man. Pigs and fowls can be fed on food which man cannot eat. Thus the shortage of wheaten flour can be made good by foods of equal value which can help to make the loaf.* Bread has hitherto formed one-third of the food of the nation ; with some butter, margarine or fat, and fresh vegetables, it is enough to sustain life and keep up the worker's energy. The bread supply can be maintained by adding the maize, oat, and barley meal to the wheaten flour, and this is the policy of the Wheat Commission. It is difficult for workers who live in tenements, and go out to work in factories, to cook foods. In towns like Glasgow and Dundee a large proportion of the population live in tenements. Thus the need for canteens at munition works is imperative. 19. The attention of the Committee has been drawn to the fact that the very existence of certain factories essential to armament output has been dependent upon proper canteen arrangements. Under the Canteen Committee of the Central Control Board, which is the responsible body for the establishment of canteens in munition works, there have been (up to October, 1917) provided some 710 canteens in works employing about 920,000 people, or about 45 per cent. of all munition workers. It must not be supposed from these figures that there are 920,000 places in these canteens, but that this is the number of workers in factories possessing more or less adequate canteens, and by arrangement of meals in shifts it is conceivable that this large number of workers might be accommodated in time of pressure. But even so, it is obvious that there is at present no canteen provision for, say, 55 per cent. of the munition workers. In other words, the canteen accommodation now in existence (with the exception of hostel canteens) is not an available instrument for the systematic rationing of the munition workers as a whole ; first, because canteens are not universal in all munition works or areas ; and, secondly, because they could not in any event cover the whole day and night requirements of all workers, particularly those engaged on 8-hour shifts. The more enlightened employers and organisers of labour now realise the importance of proper canteens in facilitating output. The new recruits are anxious to create a good impression and overtax themselves, while they lunch on buns and cakes. When the worker learns to ask for and consume a good canteen plateful of meat and vegetables improvement in health and output will not be long in making their appearance. 20. In conclusion, I desire to acknowledge the assistance received by me from my colleagues, Dr. Benjamin Moore, F.R.S., and Mr. A. Webster (who has carried out many of the analyses), and Captain Greenwood, of the Welfare and Health Section of the Ministry of Munitions. LEONARD E. HILL. October, 1917. *Cf. "The National Food Supply in Peace and War," by Prof. T.B. Wood ; Cambridge University Press, price 6d. Printed under the authority of His Majesty's Stationery Office By HARRISON AND SONS, PRINTERS IN ORDINARY TO HIS MAJESTY, ST. MARTIN'S LANE, LONDON, W.C.2. 127/NU/5/5/1/1